Idiopathic Organ Transplant Chorioretinopathy after Liver Transplantation - Maria Fernanda Abalem; Pedro Carlos Carricondo; Sergio Luis Gianotti Pimentel; Walter Yukihiko Takahashi (Case Reports in Ophthalmological Medicine)
Idiopathic organ transplant chorioretinopathy is a rare disease associated with kidney and heart transplantation. We present a case secondary to liver transplantation including its multimodal imaging, differential diagnosis, and physiopathology discussion.